CHEMİCAL ENGİNEERİNG STUDY PROGRAM, ENGİNEERİNG FACULTY, UPN UNİVERSİTY, EAST JAVA, INDONESIA - Sheykhi, Mohammad Taghi (Acta Scientiae et Intellectus, 2024)
The paper explores how the concurrent changes including improving welfare, better life conditions, literacy, work status, food intake, urban life and in general, globalization have led to human development followed by aging of population in Iran. However, aging as a global phenomenon is spreading worldwide ___ more in the Western world, and to a lesser extent in the developing world. While the number of aging people is gradually surging, yet the necessary institutions and infrastructures are not increasing that enough to cope with the needs. Though the main method of research used in the present article is empirical, yet it is preceded by theoretical and literature review. For the present research five hundred elderly people have randomly been selected, and the main hypothesis for which is: "increasing security of the elderly positively enhances their quality of life". In conclusion, the research finds out that the new generation of the aging people have new expectations and needs as compared with the previous generations.